Ultrasensitive metadevices for gas sensing - Shi, Ruxin (2018)
Surface plasmons (SPs) essentially are collective oscillations of the free electron gas density on the interface between the metal and dielectrics. Nowadays, sensors based on the surface plasmon occupy a dominant position in the development of sensing field. To solve the frequency limitation problem of the traditional localized surface plasmon resonance (LSPR) sensor, spoof localized surface plasmon resonance sensor was required to be developed especially in the microwave frequency and terahertz frequency. This paper described two kind of spoof localized surface plasmon resonance (LSPR) sensor for carbon dioxide, carbon monoxide, and nitric monoxide detection. The project mainly focuses on the materials selection and the structure design on the gas sensing on mid-infrared frequency. This design covers PEC, gold, silver and aluminum four materials and two structures: spiral structure and straight structure. All of their performances were compares in the results.